Reputation and status in Denmark’s strategic culture - Nikita E. Belukhin; Vladislav V. Vorotnikov; Svetlana Y. Dianina (Baltic Region, 2023)
The primary objective of the article is to evaluate the significance of status and allied reputation within Denmark’s strategic culture. Amongst Danish international relations scholars, there is a well-established notion that one of the key motivations for the use of military force in Danish foreign policy was the aspiration to cultivate special relations with the United States and achieve the status of a privileged ally. This status would confirm guarantees for Denmark’s national security, provide the country with an opportunity for distinctive influence in decision-making and agenda-setting in NATO, the EU, and transatlantic cooperation. A qualitative content analysis of the 2017—2018, 2019—2020 and 2022 Danish foreign policy strategies was carried out to determine the effect of such expert perceptions on the texts of the guiding foreign policy documents. The analysis highlighted and confirmed the ‘super Atlanticism’ tendencies in Denmark’s contemporary strategic culture, revealing its close ties with the Danish perception of the US as the safeguard for the liberal world order and associated multilateral institutions. Denmark’s value-driven militarised foreign political activism in the post-Cold War era is thus not only pragmatic but also ideological as it seeks to promote liberal values, democracy and human rights under American leadership. The article concludes that factoring in status and reputation in strategic culture studies may complement the explanations of security community formation, alliance strategies and the dynamics behind relations within different types of alliances.